Analysis of The Application PSAK 71 To Impairment Losses Reserve (CKPN) In Stated-Owned Enterprises of Indonesia (BUMD) In The Banking Sector: (Case study: PT. Bank Pembangunan Kalimantan Barat) - Prisila Januria Fedriata (Cita konsultindo, 2023)
PSAK 71 is officially effective in 2020, banking issuers are required to include the formation of CKPN. This study aims to determine the analysis of the implementation of PSAK 71 against the allowance for impairment losses at Regional Government Bank West Kalimantan (PT BPD KALBAR). The data analysis of this research was carried out from 2020-2022. The method used in this research is qualitative descriptive. The results of this study are the determination of CKPN, recognition, and measurement of CKPN PT. BPD Kalbar compliance with PSAK 71. PT. BPD Kalbar recognizes and measures allowance for losses for financial instruments totaling ECL - 12 months if credit risk is low and there is no significant increase. On the other hand, PT. BPD Kalbar will recognize and measure the allowance for losses for financial instruments based on the ECL lifetime of the financial instrument if the credit risk of the financial instrument has experienced a significant increase from the time of initial recognition. PT. BPD Kalbar uses forward-looking information.